Design of two-stage fish spear-shaped UWB bandpass filter with sharp selectivity and good out-of-band performances. Issue 9 (14th August 2017) - Jhariya, Dharmendra Kumar; Mohan, Akhilesh; Sinha, Manoranjan
Abstract : In this paper, a novel two-stage fish spear-shaped multimode resonator (MMR)-based ultra wideband (UWB) bandpass filter (BPF) is presented. The fish spear-shaped MMR is loaded with stepped impedance resonator in order to improve the out-of-band performance of the proposed filter. The proposed UWB BPF filter has fractional bandwidth better than 110%. In order to validate the present design approach, the filter is fabricated on RT/Duroid 5880 having dielectric constant 2.2, thickness 0.787 mm and loss tangent of 0.0009. The measured passband bandwidth of the filter is from 3.3 to 11.85 GHz, with insertion loss of 1.5 dB and return loss better than 12 dB in the passband. The proposed filter has sharp selectivity and upper stopband with 20 dB attenuation from 12 to 24 GHz.